The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1007/s00220-019-03573-7
|View full text |Cite
|
Sign up to set email alerts
|

Modulation Equation and SPDEs on Unbounded Domains

Abstract: We consider the approximation via modulation equations for nonlinear SPDEs on unbounded domains with additive space time white noise. Close to a bifurcation an infinite band of eigenvalues changes stability, and we study the impact of small space-time white noise on this bifurcation.As a first example we study the stochastic Swift-Hohenberg equation on the whole real line. Here due to the weak regularity of solutions the standard methods for modulation equations fail, and we need to develop new tools to treat … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…Moreover, it would be interesting to extend the present considerations to SPDEs on unbounded domains that are intensely studied over the past few years, cf. [4,11]. Such studies are currently in progress and will be reported in future publications.…”
Section: Conclusion and Future Challengesmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, it would be interesting to extend the present considerations to SPDEs on unbounded domains that are intensely studied over the past few years, cf. [4,11]. Such studies are currently in progress and will be reported in future publications.…”
Section: Conclusion and Future Challengesmentioning
confidence: 85%
“…Nevertheless, we will not focus on this case here. See [11] for the full approximation of Swift-Hohenberg perturbed by space-time white noise on the whole real line, [21] in the case of a simple one-dimensional noise, and [12] for large domain.…”
Section: Introductionmentioning
confidence: 99%
“…In [7] the authors study large domains, where the dominating pattern is slowly modulated in space and the amplitude equation is thus an SPDE of Ginzburg-Landau type. See also [2] for an example of a fully unbounded domain.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous extensions of our results are imaginable. While including quadratic or higher order nonlinearities seem to be technical but possible, unbounded or large domains as in [2] are a more challenging question. Moreover, it would be desirable to extend these results to SPDEs perturbed by rough nonlinear multiplicative noise.…”
Section: Introductionmentioning
confidence: 99%
“…For the case of SPDEs on unbounded domains the effective equation is no longer an SDE, but the reduced model is still given as an infinite dimensional SPDE. For details see [22] in the case of a simple one-dimensional noise, [7] for large domains and [2,19] for results with space-time white noise and on an unbounded domain. Here we will focus on the case of bounded domains only.…”
Section: Introductionmentioning
confidence: 99%